Evaluation of the Visual Demands of Digital Billboards Using a Hybrid Driving Simulator. (September 2014) - Schieber, Frank; Limrick, Kevin; McCall, Robert; Beck, Andrew
Digital billboards (DBBs) are designed to present a virtually limitless stream of information intended to acquire the attention of passing motorists. Unfortunately, very little published research has been conducted to examine how much information drivers can extract during these epochs, or how the acquisition of this information impacts driving performance. Large-format signs are difficult to study using conventional driving simulators because their displays lack the spatial resolution needed to adequately render signs at distances greater than 100-ft. The current study used a hybrid video/mechanical driving simulator to overcome such limitations. Lane keeping, eye gaze position and reading performance were monitored while participants read digital billboards displaying 4, 8 and 12 words while traveling at 25 and 50 MPH. Results indicated that drivers gradually drift away from the centerline during the DBB inspection interval, and then execute large / sudden compensatory steering inputs to re-establish their position in the center of the lane after the billboard had been overtaken. Conditions leading to visual processing overload are iden-tified and some preliminary guidelines for the design and placement of roadside DBBs are proposed.